THE STUDY OF AVIATION SERVICE INDUSTRY CURRICULUM’S COMPATIBILITY WITH GROWING AVIATION SERVICE INDUSTRY IN THAILAND - Aksornkitti, Sauce (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The objectives of this research were to: 1) understand preferred characteristics of graduates in Aviation industry and 2) utilize the results as guidelines for creating and developing Aviation Service Industry Curriculum in accordance with aviation industry and strengthening vocational competency of aviation employees based on the National Strategy on Developing and Strengthening Human Capital policy. A questionnaire was sent to 400 stakeholders in aviation service industry. The data was analyzed by using t-test and F-test statistical approaches. The results revealed the compatibility of Aviation Service Industry Curriculum and each growing aspect of aviation service industry in Thailand. It was found that the average values ranked from highest to lowest for the skills of interpersonal relationship and responsibility, psychomotor, morality and ethics, numerical analysis and communication and information technology, knowledge, and cognition were 4.52, 4.51, 4.49, 4.26, 4.23, and 4.22, respectively. The results from personal factors of participants indicated that there was no difference in gender, whereas age and job tenure did have differences. The research findings can be used as guidelines for constructing and improving the curriculum to suite the aviation service industry and for expanding the knowledge to other curricular related to service industry in Thailand.